IMPLEMENTATION OF AUGMENTED REALITY TECHNOLOGY FOR MARKETING STRATEGIES AND USER EXPERIENCE IN RETAIL SME INDONESIA - Fernando, Ricky; Turangan, Kerenhapukh Piay; Suphangat, Felix Mario; Kembau, Agung Stefanus (Universitas Nusa Cendana, 2024)
This study investigates the impact of Augmented Reality (AR) technology on the customer experience at Miracle MacBook, contextualized within the Indonesian SME landscape. AR enhances user engagement by blending virtual elements with the physical world, offering an immersive shopping experience. The study uses interviews, observations, surveys, and analytical frameworks (STP, SWOT, Porter's Five Forces, VRIO, SDLC, and Augmented Reality Maturity Model) to assess the impact of AR as a business transformation. The results highlight the significant benefits of implementing AR to increase consumer engagement and loyalty in a competitive SME environment. The study recommends implementing AR technology to increase consumer trust and reduce reliance on price competition for Miracle MacBook and similar SMEs in Indonesia. Strategically integrating AR into online platforms can mitigate existing weaknesses and threats by enriching transactional experiences and differentiating brands through innovation. Recommendations include initiating AR pilot projects on websites with basic 3D interaction features, investing in advanced AR capabilities, and expanding AR applications to enhance customer service and marketing initiatives. Ongoing evaluation and training programs are essential to sustain AR innovation and meet evolving consumer demands. By strategically embracing AR, SMEs like Miracle MacBook can increase customer engagement, drive sales growth, and strengthen their market position amidst the digital transformation of Indonesia’s SME sector. Keywords : Augmented Reality; User Experience; AR Prototype; Small Business Enterprise